TINJAUAN HUKUM PIDANA DAN HUKUM PIDANA ISLAM TERHADAP PENIMBUNAN DAN PENJUALAN BBM BERSUBSIDI - Sitompul, Ozi Suhendra; Lubis, Syaddan Dintara (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research aims to describe legal sanctions for perpetrators of criminal acts of hoarding and selling subsidized fuel according to criminal and Islamic criminal laws. The research method is empirical legal research using a legal sociological approach. Interviews or observations obtain primary data, and secondary data is from books, articles, or other reading sources. The data was analyzed using content analysis and case study analysis. So researchers can explore, analyze and interpret empirical data related to the social aspects of law. The results of this research explain that hoarding is prohibited in positive criminal law and Islamic criminal law. Sanctions in positive law are regulated in the Oil and Gas Law no. 22 of 2001 article 55, with a maximum penalty of imprisonment of 6 (six) years and a maximum fine of IDR 60,000,000,000.00 (sixty billion rupiah). Meanwhile, hoarding is known as the ta'zir punishment in Islamic criminal law. This illustrates that in the context of criminal law. However, there may be similarities in the conception of certain criminal acts, sanctions and punishment approaches can differ based on different legal bases.